2021
DOI: 10.3390/antiox10091420
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D Is Associated with Antioxidant Potential in Peri-Parturient Cows

Abstract: Dairy cows experience increased oxidative stress during periods of transition such as at the cessation of lactation and around the periparturient period, thus increasing disease risk. Despite routine supplementation of transition cow diets with certain vitamins in an attempt to mitigate oxidative stress, there is no currently available data directly linking vitamin supplementation with antioxidant potential (AOP) in transition cows. The objective of this study was to determine the association between serum vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…As well known, vitamin D 3 is the strong antioxidant which may inhibit LP in tissues. Vitamin D 3 protects cells membranes from destroying by free radicals, supports their antioxidant capacity (considerably decreases iNOS expression, ROS and malondialdehyde production) [17,18]. In this way vitamin D 3 inhibits LP and reduces OS.…”
Section: Results and Their Discussionmentioning
confidence: 99%
“…As well known, vitamin D 3 is the strong antioxidant which may inhibit LP in tissues. Vitamin D 3 protects cells membranes from destroying by free radicals, supports their antioxidant capacity (considerably decreases iNOS expression, ROS and malondialdehyde production) [17,18]. In this way vitamin D 3 inhibits LP and reduces OS.…”
Section: Results and Their Discussionmentioning
confidence: 99%
“…Vitamin D also played an important role in calcium absorption (Eder and Grundmann, 2022). Calcium ion played a role in myometrial contractions in the third phase of labor (Strickland et al, 2021). Sunlight was useful for vitamin D synthesis in cow skin (Weir et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, vitamin D treatment has been associated with increased cell viability and the inhibition of S. aureus adhesion and invasion in bovine mammary epithelial cells, underscoring its potential significance in mastitis prevention ( 202 ). Consistently, a recent published article has demonstrated that vitamin D and its metabolites hydroxyvitamin D [25(OH)D] with a concentration of 20-400 ng/ml has shown a positive role on bovine immune cells, antioxidant response and could be consider as therapeutic agent for mastitis prevention ( 203 205 ).In light of the available literature, it is evident that vitamin D holds a central position in bolstering dairy cattle immunity and potentially alleviating bovine mastitis. However, it is worth noting that further comprehensive investigations are warranted to gain a deeper understanding of its precise mechanisms and potential therapeutic applications in this context.…”
Section: The Role Of Vitamins Supplementation In Mastitis Alleviationmentioning
confidence: 91%